2012
DOI: 10.1097/mph.0b013e318253f0e1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Childhood Pancreatoblastoma Arising From the Tail of the Pancreas

Abstract: Pancreatoblastoma is a rare pancreatic tumor. In this study, 3 cases of childhood pancreatoblastoma that arise from the tail of the pancreas were reported. Abdominal pain and vomiting were observed in 1 case considering the huge size of the tumor. The other 2 patients, who were previously well, complained of a mass in the abdomen after a casual physical examination. Elevated serum α-fetoprotein levels were noted in all cases. Imaging findings indicated a well-defined heterogeneous large mass in the left retrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…PBs comprises only 0.5% of pancreatic non-endocrine tumours and share similar histological and morphologic features with hepatoblastomas that secrete α-fetoprotein (AFP) (6,15). Although reported with high prevalence (6), in our study, we recorded only one case of this type of malignancy in a child presenting with a large abdominal mass (No.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…PBs comprises only 0.5% of pancreatic non-endocrine tumours and share similar histological and morphologic features with hepatoblastomas that secrete α-fetoprotein (AFP) (6,15). Although reported with high prevalence (6), in our study, we recorded only one case of this type of malignancy in a child presenting with a large abdominal mass (No.…”
Section: Discussionmentioning
confidence: 70%
“…PB is less aggressive in children when compared with adults, therefore surgery is the optimal treatment and complete resection of the tumour provides the best prognosis (6). Moreover, adjuvant chemotherapy is not recommended if the tumour can be completely excised (15). However, we performed a true-cut biopsy in case 2 who had a large mass located in the head of the pancreas and treated him by chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatoblastoma is usually incidentally found because most of the time it is asymptomatic. In a study by Xu et al [9] where they reported three cases of PB, two of the three cases were only identified after finding an abdominal mass in rather a casual abdominal examination.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was suggested pancreatoblastoma originates in the ventral pancreatic bud as a result of abnormal embryological development [ 6 , 7 ], which would explain why it is typically found at the head of the pancreas. However, it can sometimes be found in the tail of the pancreas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%